2016
DOI: 10.1097/mnh.0000000000000228
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria as therapeutic targets in acute kidney injury

Abstract: PURPOSE OF REVIEW: Mitochondria are complex intracellular organelles with a variety of important functions. The kidney tubule is densely packed with mitochondria, and mitochondrial dysfunction is thought to be central to the pathogenesis of acute kidney injury (AKI). Mitochondria therefore represent potential targets for novel therapeutic interventions in AKI. RECENT FINDINGS: Several mitochondrial targeted approaches have shown promise in recent preclinical studies of AKI, including measures to: reduce oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 53 publications
0
53
0
Order By: Relevance
“…It has been identified that normally elongated mitochondria in the proximal tubule rapidly fragment in response to cisplatin [29]. Drp1 is the master regulator of mitochondrial morphology [30].…”
Section: Discussionmentioning
confidence: 99%
“…It has been identified that normally elongated mitochondria in the proximal tubule rapidly fragment in response to cisplatin [29]. Drp1 is the master regulator of mitochondrial morphology [30].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that MtD is mainly observed in acute kidney injury and CKD [28,29]. Our previous study demonstrated that NLRP3 deficiency may attenuate renal fibrosis by improving MtD in a mouse unilateral ureteral obstruction model for CKD [22].…”
Section: Discussionmentioning
confidence: 99%
“…Renal tubules are densely packed with mitochondria. Mitochondrial dysfunction is thought to be a key mechanism in the pathogenesis of AKI [10]. Under the physiological conditions, excessive inhibition the mitochondrial activity could be toxic to cells and organs.…”
Section: Discussionmentioning
confidence: 99%
“…The renal tubule is densely packed with mitochondria to generate sufficient ATP via oxidative phosphorylation (OXPHOS) to power the solute transport in the kidney [10]. Besides the energy production, mitochondria also play important roles in mediating the signaling transduction, cell proliferation, cell growth, and cell death [11,12].…”
Section: Introductionmentioning
confidence: 99%